The Effect of Environmental Accounting Disclosures on Financial Performance and Stock Performance: Pengaruh Pengungkapan Akuntansi Lingkungan Terhadap Kinerja Keuangan dan Kinerja Saham - Mashudi, Afinia Arini; Nurasik, Nurasik (Indonesian Journal of Law and Economics Review, 2018)
The aim of this research is to know and analyze the effect of Enviromental Accounting Disclosures on Financial Performance and Stock Performance. The sample of company in this research is company in the general mining sector and plantation sector which are registered in Bursa Efek Indonesia. Based on the problem on this research, then the type of this research is uses quantitative research. The statistical technique that used to verify hypothesis is simple linear regression. The samples were taken purposively as many as 9 sample companies that consist of 5 companies of general mining sector and 4 companies of plantation sector. The result of this research stated that the disclosure of enviromental accounting has a significant effect on company performance because of the significance value is below 0.05 percents. The disclosure of enviromental accounting has no significant effect on stock performance because of the significance value is above 0.05 percents.